2022
DOI: 10.1002/ente.202101051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Charge Acceptance Tests on Lead–Acid Cells for Carbon Additive Screening

Abstract: Including a certain amount of carbon in the negative active material is currently the state‐of‐the‐art method to improve the dynamic charge acceptance (DCA) of lead–acid batteries. The DCA is a key parameter of batteries used in microhybrid cars where brake energy recuperation is implemented. To find the optimal carbon additive, it is essential to test the carbon both in short‐term and long‐term tests. This work investigates the long‐term and short‐term DCA of 2 V, 2.5 Ah lead–acid cells and correlates the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…It has been shown that innovative negative electrode technologies, such as carbon additives or organic expanders in the negative active material (NAM), allow for up to three times more stabilized DCA after several months in operation [10]. Additives substantially influence the structure of porous active materials [11]. Moreover, they influence the processing of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that innovative negative electrode technologies, such as carbon additives or organic expanders in the negative active material (NAM), allow for up to three times more stabilized DCA after several months in operation [10]. Additives substantially influence the structure of porous active materials [11]. Moreover, they influence the processing of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the structural investigations that were carried out and described in Part I of this article, the influence of carbon additives on the DCA of LABs has also been investigated in another article. [27] In general, the charge acceptance values obtained from the Charge Acceptance Test 2 are higher than the ones according to the DCA EN test for all battery/cell types. This general trend can be explained by the test procedure itself.…”
Section: Influence Of Cell Composition On the Charge Acceptancementioning
confidence: 84%
“…In addition to the structural investigations that were carried out and described in Part I of this article, the influence of carbon additives on the DCA of LABs has also been investigated in another article. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…[114] As a shiny and soft metal that belongs to a post-transition metal group in the periodic table, Pb has a versatile application in industry. [115][116][117] The recycled Pb-containing compounds from degraded PSCs can be used not only for fabricating PSCs but also as raw materials in other industries, such as car batteries [118,119] and anodes in wastewater treatment. [120,121] In comparison with obtaining new materials through mining, transportation and smelting, recycling Pb-containing materials can greatly reduce mining waste, environmental pollution and energy consumption.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%